Fluorescence Imaging System Using High Power LED to Generate Oral Auto-fluoerscence of Sprague dawley Rat - Sa’adah, Lailis; Rakhmadi, Frida Agung; Widyaningrum, Rini (Proceeding International Conference on Science and Engineering, 2017)
It is difficult to distinguish oral cancer and normal oral mucosa in clinical examination. Hence, it is important to develop a diagnostic tool to aid clinical practitioners to examine and diagnose abnormalities in oral cavity. One of methods applied for this purpose was based on tissue auto-fluorescence. The purpose of this study was to develop a fluorescence imaging (FI) system using High Power LED (HPL) as excitation source. There were 3 HPL with different wavelengths used in this study, i.e. 385, 420, and 455 nm. The system was aimed to generate as well as to detect the auto-fluorescence effect of oral cavity in Sprague dawley rats. This study was done in 6 steps, i.e. development of FI system, early test of FI system using coconut oil, palm oil, olive oil, eucalyptus oil, and pure water as samples, followed by finishing of the system, image acquisition of oral cavity auto-fluorescence from 3 samples of Sprague dawley rats, and the last step was data analysis to determine the best wavelength of HPL for FI system developed in this study. Auto-fluorescence images were obtained by exposing samples by using HPL, then auto-fluorescence effect emitted by samples were captured using Canon EOS D600 camera. Auto-fluorescence intensity from images were analyzed using MATLAB R2008a. Results of this study showed that the best HPL wavelength used for the FI system was 385 nm that was captured with filter in the camera. The auto-fluorscence image produced by using HPL 385nm was showed the lowest intensities.